2006
DOI: 10.1074/jbc.m511152200
|View full text |Cite
|
Sign up to set email alerts
|

A Uracil-DNA Glycosylase Inhibitor Encoded by a Non-uracil Containing Viral DNA

Abstract: Uracil-DNA glycosylase (UDG) is an enzyme involved in the base excision repair pathway. It specifically removes uracil from both single-stranded and double-stranded DNA. The genome of the Bacillus subtilis phage 29 is a linear double-stranded DNA with a terminal protein covalently linked at each 5-end. Replication of 29 DNA starts by a protein-priming mechanism and generates intermediates that have long stretches of single-stranded DNA. By using in vivo chemical cross-linking and affinity chromatography techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 48 publications
(17 reference statements)
1
44
0
Order By: Relevance
“…To study the in vivo role of protein p56, we used the same DNA preparations to transfect p56-producing cells to find out the effect of inhibiting the host UDG on the infectivity of uracilcontaining 29 DNA. These cells, which carry the recombinant plasmid pPR53.p56, constitutively synthesize protein p56 at levels only slightly lower than those detected at 40 min of phage infection (10). The results revealed that the infectivity of uracilcontaining DNAs increased substantially in B. subtilis cells whose UDG activity was inhibited because of the presence of p56, in comparison with p56 nonproducing cells (Fig.…”
Section: Inhibition Of Host Udg By Protein P56 Enhances Virus Productmentioning
confidence: 53%
See 4 more Smart Citations
“…To study the in vivo role of protein p56, we used the same DNA preparations to transfect p56-producing cells to find out the effect of inhibiting the host UDG on the infectivity of uracilcontaining 29 DNA. These cells, which carry the recombinant plasmid pPR53.p56, constitutively synthesize protein p56 at levels only slightly lower than those detected at 40 min of phage infection (10). The results revealed that the infectivity of uracilcontaining DNAs increased substantially in B. subtilis cells whose UDG activity was inhibited because of the presence of p56, in comparison with p56 nonproducing cells (Fig.…”
Section: Inhibition Of Host Udg By Protein P56 Enhances Virus Productmentioning
confidence: 53%
“…We recently proposed that this inhibition is essential for an efficient infection, because the action of UDG on 29 ssDNA molecules that contain uracils would be deleterious for 29 DNA replication (10,11). To test this hypothesis, we have studied the consequences of uracil misincorporation on in vitro 29 DNA replication when UDG is present.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations